2011
DOI: 10.1371/journal.pone.0023963
|View full text |Cite
|
Sign up to set email alerts
|

Genome Profiling (GP) Method Based Classification of Insects: Congruence with That of Classical Phenotype-Based One

Abstract: BackgroundRibosomal RNAs have been widely used for identification and classification of species, and have produced data giving new insights into phylogenetic relationships. Recently, multilocus genotyping and even whole genome sequencing-based technologies have been adopted in ambitious comparative biology studies. However, such technologies are still far from routine-use in species classification studies due to their high costs in terms of labor, equipment and consumables.Methodology/Principal FindingsHere, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 30 publications
(49 reference statements)
0
10
0
Order By: Relevance
“…Finally, the GP analysis was able to discriminate differences between close genomes (i.e., those generated during short term body growth or differentiation), such as neighboring leaf sections (~mm distance) and microcubes of brain slices (~200 μm distance). The GP method and genome distance have already been used with success in several other studies . This evokes a novel, difficult problem in rationalizing the total amount of mutation, μ(g), introduced in a previous study , where the genome distance between two leaves taken from different branches was dealt with as follows: μfalse(normalgfalse)normalμnormalc·g,where μ c and g represent the constant mutation rate (/base/generation) of cells and the number of generations of cells, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Finally, the GP analysis was able to discriminate differences between close genomes (i.e., those generated during short term body growth or differentiation), such as neighboring leaf sections (~mm distance) and microcubes of brain slices (~200 μm distance). The GP method and genome distance have already been used with success in several other studies . This evokes a novel, difficult problem in rationalizing the total amount of mutation, μ(g), introduced in a previous study , where the genome distance between two leaves taken from different branches was dealt with as follows: μfalse(normalgfalse)normalμnormalc·g,where μ c and g represent the constant mutation rate (/base/generation) of cells and the number of generations of cells, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…As is the case with all methodologies, the GP method has its own limitation: it contains a stochastic property in the calculation of PaSS values (also their derivative genome distances) (Kouduka et al, 2006;Ahmed and Nishigaki, 2008), which becomes more significant when the relationship of two species is distant although such a stochastic effect is negligible for sufficiently close species as shown in this study (Watanabe et al, 2002). Empirically, we have already clarified that the range of effective applications is unexpectedly wide; e.g., the genera of insects (Odonata (i.e., dragonfly), Orthoptera (i.e., grasshopper), Hemiptera (i.e., cicada), Lepidoptera (i.e., butterfly), Coleoptera (i.e., beetle), and other related taxa) could be classified congruently with that provided by the classical phenotype-based method (Ahmed et al, 2011). Through the success of this study, fungal species of Trichosporon were shown to be genomically closer than the application limit of the GP approach.…”
Section: --mentioning
confidence: 89%
“…In this context, a simple and universal method to identify and classify species has been developed: the genome profiling (GP) method (Ahmed et al, 2011;Hamano et al, 1996;Kouduka et al, 2007;Naimuddin et al, 2000;Watanabe et al, 2002) which is mainly based on the statistical concept of random sampling and the rapid acquisition of sequence information. GP can be highly powerful and reproducible in species identification due to i) reproducible sampling of DNA fragments from the original genomic DNA by random PCR, which can employ a defined set of primers for any kind of organisms, ii) acquisition of the sequence--5 -derived information without sequencing by using µTGGE (temperature gradient gel electrophoresis) to which random PCR products can be directly applied without purification of DNA fragments, and iii) normalization of the acquired data using internal references, which leads to obtaining species-specific data.…”
Section: Introductionmentioning
confidence: 99%
“…There is a great need to explore more deeply the formation of these secondary structure patterns and their role in 3′-end maturation at the genome-wide level. It is clear from several studies that integrating secondary structure features of mRNA during siRNA design generates more functionally potent siRNA (Tafer et al, 2008; Ahmed and Raghava, 2011). Therefore, new algorithms integrating both sequence and structural features may be helpful for predicting more accurate PAS’s.…”
Section: Functional Elements Of An Mrna Moleculementioning
confidence: 99%